Geopolítica y geoeconomía en América Latina y el Caribe: desigualdad y conflictos internacionales en clave latinoamericana - Flores-Flores, Daniel (2024)
Within the framework of Latin American geopolitics, the rich and diverse tradition of critical social thought presents itself as a valuable resource for understanding contemporary transformations and addressing the challenges posed by current global risks. This article proposes to analyze inequality and international conflicts in Latin America and the Caribbean from a critical Latin American and Caribbean perspective, using the approach of the geopolitics of security and the geoeconomics of dependency. These approaches not only offer a historical and structural understanding, but are also essential to address both international security and the persistent economic inequality gaps in our contemporary reality.